2019
DOI: 10.1136/bmjophth-2018-000237
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of choroidal thickness measurements with Spectralis OCT images

Abstract: ObjectiveTo investigate the repeatability of choroidal thickness measurements determined from enhanced depth imaging optical coherence tomography (EDI-OCT) images of eyes after wearing single-vision spectacles (SV) and orthokeratology (ortho-k) lenses.Methods and analysisTwo EDI-OCT images of 40 children (SV: 20, ortho-k: 20) taken at a single visit were analysed twice. Subjects in the ortho-k group had been wearing ortho-k for 1–4 weeks. The choroidal thickness was determined from each image using a graph the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Li et al18 also suggested that the subfoveal choroidal thickening during orthokeratology treatment probably served as a predictor for the long-term effectiveness of the treatment. However, despite the choroidal changes observed and their significance in the statistical model in this study, the interimage (examining two chorio-retinal images captured from the same eye in the same measurement session) coefficient of repeatability of the subfoveal choroidal thickness measurement using a semiautomated method in orthokeratology-treated subjects was only 10 μm 35. This implies that the maximum mean treatment group changes observed in this study approached the coefficient of interimage repeatability of our technique, and therefore there is some uncertainty whether the observed changes in choroidal thickness are genuine.…”
Section: Discussionmentioning
confidence: 62%
“…Li et al18 also suggested that the subfoveal choroidal thickening during orthokeratology treatment probably served as a predictor for the long-term effectiveness of the treatment. However, despite the choroidal changes observed and their significance in the statistical model in this study, the interimage (examining two chorio-retinal images captured from the same eye in the same measurement session) coefficient of repeatability of the subfoveal choroidal thickness measurement using a semiautomated method in orthokeratology-treated subjects was only 10 μm 35. This implies that the maximum mean treatment group changes observed in this study approached the coefficient of interimage repeatability of our technique, and therefore there is some uncertainty whether the observed changes in choroidal thickness are genuine.…”
Section: Discussionmentioning
confidence: 62%
“…A greater initial choroidal thickening after commencing ortho-k is associated with less axial eye growth over a one year period [368], which suggests that short-term changes in the choroid may be a biomarker for longer-term eye growth. While some commercially available posterior segment optical coherence tomographers allow high resolution imaging of the retina and choroid (~4 μm axial resolution), the intraobserver and inter-scan coefficient of repeatability for measures of subfoveal choroidal thickness is ~10 to 20 μm in children [369,373] and adults [374][375][376]. Improvements in optical coherence tomography imaging, such as higher wavelength instruments that allow enhanced imaging of the choroid-scleral interface or automated image analysis procedures that improve choroidal segmentation, may be of benefit in future studies of choroidal thickness in children treated with ortho-k.…”
Section: The Choroidmentioning
confidence: 99%
“…Enhanced depth imaging OCT with a star scan consisting of six line scans radially centred at the fovea was used. They found CRs of 7.08 and 10.06 µm for SVS and OKL, respectively (Lau et al 2019). The second study was on healthy young adults using enhanced-depth imaging OCT centred at the fovea covering 55°9 45°containing 37 horizontal line scans.…”
Section: Discussionmentioning
confidence: 99%